VEGF-C Serum Level as Predictor Lymph Node Metastasis in Advanced Stage Cervical Cancer - PATIYUS AGUSTIANSYAH (Indonesian Journal of Cancer, 2014)
The aim of this study to identify correlation between VEGF-C and lymph node metastasis in advanced stage cervicalcancer in Dr. Hasan Sadikin General Hospital Bandung from April to August 2013.Cross sectional study from 30 patients diagnosed with advanced stage Cervical Cancer (IIB IVA). We performedtransperitoneal lymphadenectomy pelvic and para-aortic and measuring VEGF-C serum with ELISA priorchemoradiation.Results : 17/30 patients (56.7%) metastasis to pelvic lymph nodes and 4/30 pastients (13.3%) metastases to para-aorticlymph nodes. VEGF-C > 5333 pg/mL has a metastasis risk to pelvic lymph node 21.6 times with 94% sensitivity; 84.6%specificity; 88.9% positive predictive value; and 84.6% negative predictive value. Meanwhile VEGF-C > 8915.5 pg/mL hasa metastasis risk to para-aortic lymph node 15 times with 75% sensitivity, 100% specificity, 100% positive predictivevalue and 96.3% negative predictive value in advanced stage cervical cancer.Conclusion: a significant correlation between VEGF-C serum level with lymph node metastasis (pelvic and para-aortic)(p < 0.05)